2014
DOI: 10.1093/jxb/eru014
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a root hair-less line of Arabidopsis thaliana under physiological stresses

Abstract: SummaryRoot hairs of Arabidopsis play significant roles in the absorption of water and several minerals, secretion of acid phosphatases and organic acids, and anchoring of roots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 67 publications
3
71
0
1
Order By: Relevance
“…Studies with root hairless mutants in Arabidopsis have indicated that root hairs contribute significantly to phosphorus acquisition and offer plants a competitive advantage under limited phosphorus availability Lynch, 1996, 2001;Brown et al, 2012). The significance of root hairs in nutrient acquisition was recently studied in the root hair-defective transgenic line NR23 of Arabidopsis (Tanaka et al, 2014). Compared with the wild type, NR23 plants exhibited decreased shoot biomass when grown under most nutrient deficiencies tested and accumulated less calcium, potassium, phosphorus, sulfur, boron, copper, and zinc in their shoots.…”
Section: Role Of Root Hairs For Nutrient Acquisitionmentioning
confidence: 99%
“…Studies with root hairless mutants in Arabidopsis have indicated that root hairs contribute significantly to phosphorus acquisition and offer plants a competitive advantage under limited phosphorus availability Lynch, 1996, 2001;Brown et al, 2012). The significance of root hairs in nutrient acquisition was recently studied in the root hair-defective transgenic line NR23 of Arabidopsis (Tanaka et al, 2014). Compared with the wild type, NR23 plants exhibited decreased shoot biomass when grown under most nutrient deficiencies tested and accumulated less calcium, potassium, phosphorus, sulfur, boron, copper, and zinc in their shoots.…”
Section: Role Of Root Hairs For Nutrient Acquisitionmentioning
confidence: 99%
“…The importance of root hairs for water uptake was shown by comparing wild-type Arabidopsis plants with hairless root mutants. Due to the reduced ability of the root hairless mutants to absorb water, they are more sensitive to drought, salinity and heat stress [40]. In barley, root hairs improved root penetration into hard, compact soils, a crucial feature for plant establishment [41].…”
Section: Controlling Water Uptake Through Roots Architecturementioning
confidence: 99%
“…The impaired responses of various root hairless mutants to altered nutrient conditions indicate the necessity for proper adjustment of root hair development for optimum interaction with the environment (Tanaka et al, 2014). Consequently, root hair length and density are constantly optimized to current environmental demands (Kochian, 1995;López-Bucio et al, 2003;Wang et al, 2008;Giehl and von Wirén, 2014).…”
Section: Rsl Genes As Integrators Of Developmental and Environmental mentioning
confidence: 99%